The Effect of Watering on Rice Washing Water,MSG Water, and AC (Air Conditioner) Wastewater on Yields Components and Tomato Yields (Lycopersicon esculentum L.) in the Deep Peatland - Hariyadi, SP, MP (Universal Institute of Professional Management, 2020)
The purpose of this study is to determine the effect of rice washing water, MSG water, and AC waste water (air conditioner) on yield components and yields of Tomato (Lycopersicon esculentum L.) plants planted in the Deep Peat Soil. This study used a randomized block design (RBD) with 3 factors: rice washing water of 3 levels (0 ml.liter-1; 500 ml.liter-1; 1000 ml.liter-1); MSG water in 3 levels (0 g.liter-1; 3 g.liter-1; 6 g.liter-1); and AC wastewater as much as 2 levels (0 ml.liter-1; 200 ml.liter-1). The parameters observed were the first flowering, fruit diameter, number of fruit plants, fruit weight per plant, average fresh fruit weight, and fruit weight per hectare of tomato plants. The results showed that the interaction of rice washing water and MSG water significantly affected the parameters at first flowering and fruit weight per tomato plant. The single factor of rice washing water and MSG water each had a significant effect on all yield component parameters and yield of tomato plants. The single factor of AC wastewater has a significant effect on all parameters of yield and yield components of tomato plants except on the number of fruits and fruit weight per hectare of tomato plants. Provision of the best rice washing water with a dose of 1000 ml.liter-1; MSG water at a dose of 6 g.liter-1; and AC wastewater at a dose of 200 ml. liters-1.